A rare anatomical variation of the circle of Willis in a patient with an ischemic stroke - Lidija Kocbek Šaherl; Klemen Lah (Acta Medico-Biotechnica, 2023)
Purpose The cerebral arterial circuit provides collateral circulation to the brain and protects the brain from ischemia, by sustaining tissue perfusion in case of reduced or impaired blood flow through its branches. Although many random anatomical variations in the circle of Willis (CoW) are of minor importance, some increase the risk of ischemic events, aneurysm, and atherosclerosis, and play an important role in endovascular and surgical treatment planning.  Case presentation We report a rare arterial variation of the CoW diagnosed by computed tomography angiography in a patient with ischemic stroke. We found aplasia of the A1 segment of the left anterior cerebral artery and ipsilateral hypoplasia of the P1 segment of the left posterior cerebral artery.  Conclusion For neurosurgeons, neurologists, and neuroradiologists, detailed knowledge of the numerous anatomical variations in the arterial supply to the brain is crucial to make a correct diagnosis and choose the appropriate treatment. The type of CoW variation influences stroke severity and outcome, with an incomplete CoW related to more severe conditions (higher National Institutes of Health Stroke Scale scores, more severe neurological deficits, and worse neurological outcomes) and poor prognosis.